Development of a reading instructional model based on reciprocal teaching approach and scaffolding techiques to enhance English reading comprehension ability of upper secondary school students - Rotchu, Phananoi (2010)
The objectives of this paper are two folds: 1) to develop an instructional model based on reciprocal teaching approach and scaffolding techniques to enhance English reading comprehension ability of upper secondary school students and 2) to evaluate the quality of the developed instructional model by comparing the students’ English reading comprehension ability before and after taking the reading instruction employing reciprocal teaching approach and scaffolding techniques. The presentation will focus on how the model was constructed and validated. The effectiveness of the model will then be discussed after it was implemented with 45 Tenth Grade students at Bangsawanwitthayakom School.